Friction Performance of Al-10%SiCp Reinforced Metal Matrix Composites Using Taguchi Method. (22nd August 2012) - Ghosh, Shouvik; Sahoo, Prasanta; Sutradhar, Goutam
Abstract : The present paper considers the friction performance of Al-10%SiCp reinforced metal matrix composites against steel for varying tribological test parameters. The composite is prepared by stir-casting process using aluminium alloy LM6 being mixed with 10% silicon carbide by weight. The tribological tests are performed by varying applied load, sliding speed, and time. The friction performance is studied using plate-on-roller configuration in a multitribotester and optimized using Taguchi L27 orthogonal array. Analysis of variance (ANOVA) is performed to observe the significance of test parameters and their interactions on friction performance. It is observed that normal load and the interaction between normal load and speed influence the friction behaviour, significantly. The wear tracks are analyzed with the help of scanning electron microscopy.